2023
DOI: 10.21873/anticanres.16302
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 Expression Correlates With T-Cell Infiltration in Oral Leukoplakia and Predicts Cancer Transformation

Abstract: Background/Aim: The EZH2 complex is involved in cellular proliferation and modulates the immune response in cancer. Less is known about the importance of EZH2 in precancerous lesions such as oral leukoplakia (OL). The aim of the study was to explore the association between EZH2 expression, immune activation, and cancer transformation in OL. found (r=0.57, p=0.01; r=0.59, p=0.01). The number of EZH2-expressing cells in the epithelium of OL-ca was significantly higher compared to OL-non (p=0.0002). Cancer-free s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…However, it is noteworthy to say that there is limited evidence concerning the significance of immune cells at the risk of malignant transformation of OPMD. Previous works were restricted to T lymphocytes and reported significant results based on a relatively small sample size 5,6. The overall inflammatory cell reaction, including lymphoid, neutrophilic, eosinophilic, and plasmacytic cells is an independent prognostic factor for OSCC 35.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, it is noteworthy to say that there is limited evidence concerning the significance of immune cells at the risk of malignant transformation of OPMD. Previous works were restricted to T lymphocytes and reported significant results based on a relatively small sample size 5,6. The overall inflammatory cell reaction, including lymphoid, neutrophilic, eosinophilic, and plasmacytic cells is an independent prognostic factor for OSCC 35.…”
Section: Discussionmentioning
confidence: 97%
“…Inflammatory cells, and tumor cells, are a source of growth factors, cytokines, chemokines, reactive oxygen and nitrogen species, and extracellular matrix (ECM)-modifying enzymes, which would sustain cell proliferation and survival, angiogenesis, cell migration and metastasis, and DNA damage 2. In oral potentially malignant disorders (OPMD), an increase in the inflammatory reaction (IR) was observed in severe oral epithelial dysplasia (ED),3,4 and immune-infiltrating cells were associated with the risk of malignant transformation of OPMD 5,6…”
mentioning
confidence: 99%
“…There is also an association between OSCC initiation and the level of EZH2 expression. It has been indicated that high expression of EZH2 in the epithelium of oral leukoplakia, which is the most common potentially malignant disorder of oral mucosa, is linked to a greater risk of developing OSCC (76,77).…”
Section: Importance Of Ezh2 In Cancermentioning
confidence: 99%